Analisis Faktor Determinan yang Mempengaruhi Adopsi FinTech pada (UMKM Bidang Fashion di Kabupaten Kolaka) - Indah Cahyani; Ismanto Ismanto; Fitri Kumalasari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to determine: (1) the influence of performance expectancy on FinTech adoption in MSMEs in the fashion sector in Kolaka Regency. (2) the influence of effort expectancy on FinTech adoption among MSMEs in the fashion sector in Kolaka Regency. (3) the influence of Social Influences on the adoption of FinTech among MSMEs in the fashion sector in Kolaka Regency. (4) the influence of facilitating conditions on FinTech adoption among MSMEs in the fashion sector in Kolaka Regency. This research uses a quantitative method. Data collection in this research used observation, documentation, and questionnaires. The population of this research is made up of MSMEs in the fashion sector in Kolaka Regency. Meanwhile, the sample for this research was 170. Instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis techniques used in this research are outer model testing and inner model testing with Smartpls 3.0. Based on the research results, it is known that: (1) there is a negative but not significant influence of the performance expectation variable on fintech adoption, as shown by a t-statistic value of 0.776 with a P-value of 0.438. (2) There is a positive and significant influence of the effort expectancy variable on fintech adoption, as shown by a t-statistic value of 8.422 with a P-value of 0.000. (3) There is a positive and significant influence of the effort expectancy variable on fintech adoption, as shown by a t-statistic value of 25,940 and a P-value of 0.000. (4) There is a negative and significant influence of the effort expectancy variable on fintech adoption, as shown by a t-statistic value of 2.810 and a P-value of 0.005.